Sustainable Development of High‐performance Poly(ester‐imine) Biobased Thermosets - Dinu, Roxana; Cibotaru, Sandu; Swanson, David D.; Mija, Alice (Advanced science, 2025)
The massive production of materials based on petroleum derivatives and often toxic compounds generates significant environmental pollution. In this context, the development of environmentally friendly alternatives becomes crucial. This study investigates the synthesis of eco‐friendly and high‐performance poly(ester‐imine) thermosets by sustainable approaches. Starting with vanillin or syringaldehyde, the synthesis involves the introduction of imine linkages within the epoxy monomer's structure. A new strategy is used through the cross–linking of the designed epoxy monomers using anhydrides, without initiators. This approach conducts to novel poly(ester‐imine) thermosets with high performances that exceed those reported in previous studies. The thermo‐mechanical investigations show that the novel‐designed thermosets have performant properties with storage moduli at room temperature ranging between 0.3‒1.74 GPa and glass transition values between 90 and 170 °C. The Limit Oxygen Index (LOI) in the range of 24‒36%, confirms the excellent flame‐retardant properties without the addition of supplementary additives. Their low‐density values (1.05‒1.36 g cm−3) and the very low WA% ≈0.09–1.15 % after 24 h make them well‐suited for a range of uses where weight and hydrophobicity considerations are critical. The obtained results place these poly(ester‐imine) materials as promising sustainable candidates for a wide range of high‐end applications. Schiff‐based epoxy monomers derived from renewable natural resources are used to design robust structures by cross–linking with bio‐anhydrides. The resulting eco‐friendly, high‐performance thermosets feature two cleavable bonds, offering versatility for various applications. These materials exhibit properties suitable for a wide range of needs, from flexible to rigid structures, ensuring adaptability in demanding environments.